Exploring associations between interpersonal violence and prison size in Spanish prisons - Caravaca-Sánchez, Francisco (Crime & delinquency, 2019)
The majority of research based on prisons in the United States has found a positive association between prison size and inmate victimization. This study estimates rates and identifies inmate and institutional characteristics associated with victimization in the Spanish prisons, with special attention on the prison size. Data were collected from a sample of male inmates aged 18 years or older (n = 2,484) located in eight prisons in the southeast of Spain. Holding inmate characteristics constant, rates of victimization were significantly and substantively higher in larger prisons. Understanding the prison size–victimization association requires further qualitative investigation to identify whether size creates more spaces for victimization (structural opportunities) and/or lapses in supervision due to depersonalization or impersonalization (social distancing).